2011
DOI: 10.1371/journal.pcbi.1002212
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Morphological Subtyping Reveals New Roles of Caspases in Mitochondrial Dynamics

Abstract: Morphological dynamics of mitochondria is associated with key cellular processes related to aging and neuronal degenerative diseases, but the lack of standard quantification of mitochondrial morphology impedes systematic investigation. This paper presents an automated system for the quantification and classification of mitochondrial morphology. We discovered six morphological subtypes of mitochondria for objective quantification of mitochondrial morphology. These six subtypes are small globules, swollen globul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(120 citation statements)
references
References 44 publications
1
118
0
Order By: Relevance
“…The latter study as well as others (e.g. [249]) demonstrated that additional mitochondrial subtyping (i.e. using more than the three categories described above) may also be applied to account for differences in shape and appearance.…”
Section: Interpretation Of Quantitative Data For Mitochondrial Morphomentioning
confidence: 77%
“…The latter study as well as others (e.g. [249]) demonstrated that additional mitochondrial subtyping (i.e. using more than the three categories described above) may also be applied to account for differences in shape and appearance.…”
Section: Interpretation Of Quantitative Data For Mitochondrial Morphomentioning
confidence: 77%
“…Another intriguing computational approach [24] involves automated subtyping of mitochondrial morphology. We have also attempted to employ the MicroP software written by the authors for our experimental needs, however, it was similarly very difficult for us to learn due to the technical (computational knowledge) needed.…”
Section: Discussionmentioning
confidence: 99%
“…“compact” versus “branched”, “non-tubular” versus “tubular”) (Vowinckel et al, 2015). When consensus clustering was applied to automatically define morphological subtypes in mitochondrial images, a total of 19 distinct morphological clusters were identified, suggesting that mitochondrial shape complexity is under-appreciated even when a single cell type is considered (Peng et al, 2011). The diversity in mitochondrial morphology may be far greater considering the extent to which mitochondria are specialized between the various cell types (Vafai and Mootha, 2012).…”
Section: Descriptions Of Mitochondrial Morphologymentioning
confidence: 99%